Designing Healthcare Systems with an Emphasis on Relational Quality and Peace of Mind - Nurgalieva L. Leysan; Baez M. Marcos; Fiore F. Francesca; Casati F. Fabio; Marchese M. Maurizio (2018, 2018)
Title screen